The profitability of second-tier banks: essence and main influencing factors - Yeveskina, Zh.T.; Nurgaliyeva А.М.; Chaykovskaya, L.A. (BUKETOV BUSINESS REVIEW, 2021)
Object. In this article, based on the aggregate indicators of second-tier banks of the Republic of Kazakhstan, what factors and how they affect the net income of the bank is determined. Methods. During the analysis, a correlation-regression analysis of banking data was carried out using the Stata statistical package, and conclusions were drawn. Findings. To identify the factors that affect the profitability of banks, the interdependencies between the selected indicators were identified. The correlation analysis revealed the relationship between the selected factors and the bank’s net income. The density of bonds was determined by testing hypotheses calculated based on pair correlation coefficients. Conclusions. The factor analysis carried out made it possible to identify the main factors affecting the bank’s activities and assess the degree of their impact. As a result of the analysis of factors affecting the bank’s income in the aggregate indicator of second-tier banks of the Republic of Kazakhstan, the compliance of the results obtained with the expected results was determined.